Thermally Resilient Planar Waveguides in Novel nc-YSZ Transparent Ceramic by fs Laser Pulses - Castillo, Gabriel R.; Burshtein, Cecilia; Uahengo, Gottlieb; Penilla, Elías H.; Esqueda-Barrón, Yasmín; Martinez-Gil, M.; de la Cruz, Wencel; Garay, Javier E.; Camacho-López, Santiago (Frontiers in Physics, 2021)
We report on thermally resilient planar waveguide fabricated on nc-YSZ by direct fs-laser inscription in transparent nc-yttria stabilized zirconia (nc-YSZ) polycrystalline ceramics. The waveguide consisted of rectangular sections (4.5×2 mm2) on the surface of the sample. Optical characterization at 633 and 810 nm was performed. We estimate a laser-induced refractive index contrast of 10^-4. Post-fabrication thermal annealing treatments at 750 °C for 24 hours were carried out to test the resilience of the waveguide and to further reduce the waveguide losses. Our results suggest a promising potential use of nc-YSZ in harsh and high temperature demanding photonic environments.